The Past, Present and Future of Antinuclear Antibody (ANA) Testing (Canadian Rheumatology Today, 2025)
This article is in memory of Dr. Eng M. Tan (Emeritus: The Scripps Research Institute) and acknowledges the remarkable mentorship and tremendous contributions to our understanding of anti-nuclear antibodies (ANA). Dr. Tan passed away in 2024 at the age of 97. More than 70 years have passed since the discovery of the lupus erythematosus (LE) cell and the development of the LE cell test, which led to the ‘tipping point’ for the discovery of antinuclear antibody (ANA), or what should more correctly be referred to as anti-cellular antibodies (ACA). Paralleling the evolution of ANA testing based on the indirect immunofluorescence assay (IFA) on cryopreserved organ sections in the 1960s and through the early 1970s was an ‘explosion’ in the spectrum of ANA and a remarkable transition in technologies used to detect ANA. This included the transition to IFA on HEp-2 cell substrates beginning in the late 1970s. While some of the ‘octogenarian’ immunoassays such as double immunodiffusion, hemagglutination, complement fixation, radioimmunoassay, and counterimmunoelectrophoresis are fading into oblivion, the ANA IFA has prevailed because of its world-wide use as a screening test for systemic autoimmune rheumatic diseases (SARD), diagnostic criteria for autoimmune hepatitis, a risk factor for the development of uveitis in juvenile idiopathic arthritis, and the entry criterion for classification of systemic lupus erythematosus (SLE). ANA testing, once regarded the domain of rheumatologists and clinical immunologists, has witnessed a widening spectrum of clinicians using these tests because of its links to a growing spectrum of autoimmune and autoinflammatory conditions. All of this is set against the background of remarkable advances in autoantibody detection, especially the emergence of newer high-throughput (i.e., faster turn-around‑time for results), multi-analyte array technologies (MAAT). These technologies use comparatively small serum or plasma volumes and provide higher specificity while detecting a broad range of SARD autoantibodies.